(untitled) (The International Journal for Scientific Research, 2023)
This article reflects on an infinitely more revealing experience that has happened "out of space", repeating the fears and anxieties that usually occur when confronted with Verginia Wolf, but this time at Victoria Train Station in London, a historical place that increases chances of understanding stories and histories, within its spaces, an ‘unblushing’ controversy between the self and the other has been lit. As one of the five ’subalturns’ in an aggressive decolonial confrontation with a French orientalist, representing an already established demagogic way of thinking that assumes monopoly of reason against presumably five ’lackeys’ representing mystery, fantasy, margin, and mental stagnation, the most worthy occasion comes to understand Khalid Amine’s philosophies, ideas and his epistemological preoccupations. In deed, Amine’s central philosophy of " figurative identity" is full of limitless significance that logically explains the natural harmony amongst identities and cultures beyond the complexities of ethnic, cultural, and political differences. With Amine’s capacity of realising the real purposes of theatre, our capacity of binding the spaces and knitting the psychological borders go beyond the busyness of the theatrical scene at Victoria Station and the differences of the characters involved,thus concluding that ‘Furja’ ‘performance’ is that interaction between the self and the other that leads implicitly and explicitly to a continuity of ‘feedback-schleife’ to use Amin’s terms, thus constructing an everchanging identity able to comprehend the world and contribute to the diversity of human cultural wealth.